Finite element implementation of an orthotropic plasticity model for sheet metal in low velocity impact simulations. (April 2015) - Mars, J.; Wali, M.; Jarraya, A.; Dammak, F.; Dhiab, A.
Abstract: A finite element (FE) implementation of an orthotropic plasticity model for sheet metal in impact simulations is performed. An accurate description of anisotropic plasticity model is presented for obtaining reliable predictions in FE simulations of low velocity impact processes. The elasto-plastic model includes isotropic elasticity, anisotropic yielding, associated plastic flow and mixed non-linear isotropic/kinematic hardening. The material model is implemented into a user-defined material (VUMAT) subroutine for the commercial finite element code ABAQUS/Explicit to predict the numerical response of circular aluminum plate subjected to low velocity impact. The impact energy was imposed by the definition of the impactor initial velocity. The numerical results of the impact force history and impact velocity are in good agreements with the LDA experimental data. The anisotropy effect of aluminum plate under low velocity impact is studied. Highlights: .Plasticity model for sheet metal is implemented in finite element impact simulations An accurate description of anisotropic plasticity model is presented. The elasto-plastic model includes the mixed non-linear isotropic/kinematic hardening. The material model is implemented into a user-defined material (VUMAT) subroutine. The anisotropy effect of aluminum plate under low velocity impact is studied.